Overview and commentary of the CDEI's extended roadmap to an effective AI assurance ecosystem - Barrance, Ethan; Kazim, Emre; Hilliard, Airlie; Trengove, Markus; Zannone, Sara; Koshiyama, Adriano (Frontiers in Artificial Intelligence, 2022)
The Centre for Data Ethics and Innovation (CDEI) has published an AI Assurance Roadmap as part of the UK government’s AI strategy. We provide an overview of the document’s vision for a ‘mature AI assurance ecosystem’, and we survey how AI assurance will be used in the wider industry and how the CDEI will work with other organisations with the development of regulation, Industry standards, and the creation of AI assurance practitioners. We also comment on the CDEI’s roadmap and our views on the complexities of building ‘justified trust’. We also analyse the role of research in AI assurance, the current developments in the AI assurance industry, and an overview of some international regulation.